Comparative structural and dynamics study of free and gRNA-bound FnCas9 and SpCas9 proteins - Gayatri Panda; Arjun Ray (Computational and Structural Biotechnology Journal, 2022)
The introduction of CRISPR/Cas9 based gene editing has greatly accelerated therapeutic genome editing. However, the off-target DNA cleavage by CRISPR/Cas9 protein hampers its clinical translation, hindering its widespread use as a programmable genome editing tool. Although Cas9 variants with better mismatch discrimination have been developed, they have significantly lower rates of on-target DNA cleavage. Here, we have compared the dynamics of a more specific naturally occurring Cas9 from Francisella novicida (FnCas9) to the most widely used, SpCas9 protein. Long-scale atomistic MD simulation of free and gRNA bound forms of both the Cas9 proteins was performed, and their domain rearrangements and binding affinity with gRNA were compared to decipher the possible reason behind the enhanced specificity of FnCas9 protein. The greater binding affinity with gRNA, high domain electrostatics, and more volatility of FnCas9 than SpCas9 may explain its increased specificity and lower tolerance for mismatches.